Click, Like, Travel : Social Media Effect on Historical Tourism Engagement–A Case Study of Siti Nurbaya Park Gunung Padang - Sari, Windy Della; Meri Ulfa Nely; Rifdatul Husna; Rini Susanti; Siti Permata Pricilla; Zengga, Zengga; Asri Jenita; Lili Miwirdi; Agung Ar Rasyid; Selvia Ananda Wandi (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the influence of social media on tourist engagement and formulate a digital marketing strategy for the development of the historical tourist destination of Siti Nurbaya Park, Gunung Padang, in Padang City. This study uses a mixed methods approach, a combination of quantitative and qualitative methods. The quantitative research design used is explanatory research because it aims to explain the causal relationship between social media (the independent variable) and tourist engagement (the dependent variable). Meanwhile, a qualitative approach is used to deepen the results of the quantitative analysis and formulate a digital marketing strategy for the destination. The quantitative data analysis technique uses simple linear regression analysis to test the relationship between social media variables and tourist engagement. Furthermore, this study also utilizes a SWOT analysis to formulate a digital marketing development strategy for the destination. The results show that social media has a significant influence on tourist engagement, contributing 57.5%. This is reflected in the increased interest in visiting, interactions through digital media, and the tendency of tourists to provide recommendations. Current digital marketing strategies are still limited to the use of Instagram and the official website, supported by short video content. However, limited human resources, digital devices, and minimal community participation hinder optimal promotion. Based on the SWOT analysis, potential strategies include strengthening creative content, expanding the use of digital platforms, collaborating with influencers, and increasing the capacity of local communities in community-based promotion. This research is expected to provide practical contributions to the development of digital marketing strategies for historical tourism destinations, while simultaneously strengthening local cultural identity and regional tourism competitiveness.